Auditing under pressure: Investigating the impact of work-life balance on auditor well-being - Badrul Hisham, Farzana; Mohd Ramly, Suhaily; A Ghani, Norhaninah (Jurnal Evolusi, 2023)
This paper aims to investigate the factors that affect the work-life balance of auditors and how it affects their overall well-being. The auditing profession is known for its demanding nature, with long working hours, tight deadlines, and high levels of responsibility that can significantly impact auditors’ ability to achieve a balanced work and personal life. To gain in-depth insights into their experiences and perceptions regarding work-life balance, this research utilizes a qualitative research method that involves conducting semi-structured interviews with auditors. A purposive sampling approach will be used to select auditors from different levels of experience, and work environments, providing a comprehensive understanding of the challenges and opportunities auditors face in managing their work and personal life. The study will explore the strategies that auditors use to balance their professional responsibilities with personal commitments, examine the role of organizational policies and support systems in facilitating work-life balance, and investigate the impact of work-life balance on their physical and mental well-being. By providing a better understanding of the complex relationship between work-life balance and auditor well-being, this study contributes to the limited existing knowledge on this topic within the auditing profession. The findings will provide valuable insights for audit firms and policymakers in developing evidence-based policies and practices that promote work-life balance and support auditors’ well-being. Furthermore, this research aims to initiate a discussion on the significance of work-life balance within the auditing field and encourage future research endeavours to address this critical aspect of auditors’ professional lives.